2022
DOI: 10.1101/2022.09.15.508134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual-motor integration deficits in 3q29 deletion syndrome

Abstract: Purpose: 3q29 deletion syndrome (3q29del) is associated with neuropsychiatric and neurodevelopmental phenotypes. We previously reported that graphomotor weakness is present in up to 78% of individuals with 3q29del. We have now explored nuances of the graphomotor phenotype and its association with other comorbidities in this population. Methods: Participants were recruited from the online 3q29 registry (3q29deletion.org) for two days of deep phenotyping. 32 individuals with 3q29del (62.5% male) were evaluated w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Moreover, we found that the Written Communication subdomain is a relative weakness in individuals with 3q29del, which measures reading and writing skills. This is consistent with prior work by our team identifying significant deficits in visual-motor integration, particularly motor coordination and graphomotor abilities, in this population (Sanchez Russo et al, 2021, Pollak et al, 2022a, highlighting the need for fostering writing skills. Additionally, we have reported that individuals with 3q29del have relatively well-preserved expressive and social communication skills (Pollak et al, 2022b, Pollak et al, 2019; thus, communication-focused interventions should leverage these relative strengths.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we found that the Written Communication subdomain is a relative weakness in individuals with 3q29del, which measures reading and writing skills. This is consistent with prior work by our team identifying significant deficits in visual-motor integration, particularly motor coordination and graphomotor abilities, in this population (Sanchez Russo et al, 2021, Pollak et al, 2022a, highlighting the need for fostering writing skills. Additionally, we have reported that individuals with 3q29del have relatively well-preserved expressive and social communication skills (Pollak et al, 2022b, Pollak et al, 2019; thus, communication-focused interventions should leverage these relative strengths.…”
Section: Discussionsupporting
confidence: 91%
“…2021; Pollak et al . 2022a), highlighting the need for fostering writing skills. Additionally, we have reported that individuals with 3q29del have relatively well‐preserved expressive and social communication skills (Pollak et al .…”
Section: Discussionmentioning
confidence: 99%
“…Further, our team has identified previously unreported associations between the 3q29 deletion and graphomotor weakness and ADHD (Pollak et al . 2022a), as well as a staggering degree of neurodevelopmental and neuropsychiatric comorbidities in this population (Murphy et al . 2018; Sanchez Russo et al .…”
Section: Introductionmentioning
confidence: 99%